Safety assessment of a traditionally used extract from leaves of Boldoa purpurascens. (4th November 2016) - Ortega, Y. Hernandez; Mosquera, D.M. González; Galapththi, S.; Santos, B. Tamargo; González, G. Sierra; Foubert, K.; Pieters, L.; Calderon, P. Buc; Apers, S.
Abstract: Ethnopharmacological relevance: Boldoa purpurascens Cav. (Nyctaginaceae) is a plant species used in traditional medicine in Cuba as a diuretic. Aim of the study: The aim of the present investigation was to evaluate the safety profile of a hydroalcoholic extract from leaves of Boldoa purpurascens. Materials and methods: First, an experimental study to assess the oral acute toxicity at a dose of 2000 mg/kg body weight of the extract was carried out. Potential genotoxicity of the extract was evaluated using the Ames test and the micronucleus induction assay in mouse bone marrow. In the Ames test a concentration range of 50, 100, 150, 300 and 500 µg/plate was tested. In the micronucleus induction assay, doses of 500, 1000 and 2000 mg/kg of body weight were tested. For completeness, since the extract contains saponins, the evaluation of the hemolytic activity, ocular and skin irritation were included. Results: No signs or symptoms of toxicity were observed in the oral acute toxicity test (body weight at baseline, seven days and end of the experiment of 236.41±20.07, 256.81±30.44 and 240.02±26.16 respectively for the treated group). The hydroalcoholic extract from the leaves was not mutagenic in the Ames test, and no genotoxicity was observed in the micronucleus assay. A hemolysis test at concentration of 1 mg/mL confirmed hemolytic activity, which is not a safety concern since saponins are not absorbed after oral administration. In order to evaluate the percentage of protein denaturation, the ocular irritability index was calculated. The extract was found to be irritating. Finally, skin irritability was evaluated and the irritation index was equal to zero. Conclusions: Based on the toxicological evaluation of a traditionally used hydroalcoholic extract from the leaves of Boldoa purpurascens we can confirm the safety of its oral use. Graphical abstract: